House Price Determinants in Selected Countries of the Former Soviet Union - Stepanyan, Vahram (IMF Working Papers; Working Paper ;, 2010)
This paper analyses the recent boom-bust cycle in the housing markets of selected Former Soviet Union (FSU) countries. The analysis is based on a newly constructed database on house prices in the FSU countries. Our estimations suggest that house price developments can largely be explained by the dynamics of fundamentals, such as GDP, remittances, and external financing. Overall, we find that deviations of house prices from their fundamentals have not been pronounced, suggesting that house price bubbles have not been formed in the FSU countries.